2021
DOI: 10.1177/01430343211013875
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of COVID-19 anxiety on learning burnout in Vietnamese students

Abstract: It is becoming clear that the COVID-19 pandemic has had a devastating psychological impact on Vietnamese society, but little is known about its impact on Vietnamese students. In the current study, we evaluated whether anxiety of contracting COVID-19 is related to students’ learning burnout. Specifically, we tested two months into the pandemic whether this anxiety is linked to pupils’ learning exhaustion and cynicism. The data includes 652 Vietnamese students (56.3% girls) with Mage = 12.6 ( SD = 1.0). The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…Accordingly, the result of this study shows that this is the case with students. Also, this result of this study concurs with the findings of the previous studies (Fernández-Castillo, 2021 ; Jiang, 2021 ; Vu & Bosmans, 2021 ; Wang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Accordingly, the result of this study shows that this is the case with students. Also, this result of this study concurs with the findings of the previous studies (Fernández-Castillo, 2021 ; Jiang, 2021 ; Vu & Bosmans, 2021 ; Wang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…As a result, when all these situations are evaluated together, it is thought that COVID-19 student stress triggers and increases school burnout. In this regard, previous studies have concluded that stressful living conditions during the COVID-19 pandemic increase school burnout in students (Ferna ´ndez-Castillo, 2021;Jiang, 2021;Vu & Bosmans, 2021;Wang et al, 2021). In addition, studies conducted before the start of the COVID-19 pandemic found that stress is a positive predictor of school burnout (Backovic et al, 2012;Lin & Huang, 2014;Yan et al, 2018).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 96%
See 1 more Smart Citation
“…Một số nghiên cứu tại Việt Nam cũng có những kết quả tương đối giống với các nghiên cứu trên thế giới: cùng với việc phong tỏa, học tập trực tuyến có thể gây ra các vấn đề về sức khỏe tâm thần của sinh viên (Thai và cộng sự, 2020); tác động tâm lý của chứng lo âu về Covid-19 đến tình trạng kiệt sức học tập của sinh viên (Vu, 2021). Và theo hiểu biết của chúng tôi, những nghiên cứu về sức khỏe tâm thần của sinh viên trong bối cảnh đại dịch Covid-19 chủ yếu tập trung vào các vấn đề tâm lý tiêu cực: lo âu, trầm cảm, stress… Có rất ít nghiên cứu đã điều tra về sức khỏe tâm lý tích cực của sinh viên: sự hài lòng với cuộc sống, chỉ số hạnh phúc, khả năng phục hồi... Trong đó, đặc biệt, chỉ số hạnh phúc với những yếu tố tâm lý tích cực đó sẽ góp phần quan trọng giúp con người ứng phó, vượt qua những tình huống khó khăn như đại dịch Covid-19.…”
Section: đặT Vấn đề *unclassified
“…When moving from a traditional classroom to online learning, the isolated environment may increase the level of learning anxiety (Kumari et al, 2021). Recent studies have documented students' academic concerns and anxiety for online learning at home (Wang et al, 2020;Arribathi et al, 2021;Fitzgerald and Konrad, 2021;Vu and Bosmans, 2021). Zhang and Cui (2010) research noted that experienced learners have lower anxiety and frustration than beginners.…”
Section: Introductionmentioning
confidence: 99%